Cytotaxonomy of Sapindaceae with special reference to the tribe Paullinieae - Ferrucci, María Silvia (2000)
In this paper are reported the chromosome numbers for 19 South American species of the tribe Paullinieae, with ten of them representing new records while previous reports are confirmed for other 9 species. These results are compared with a review of the karyology of the whole family, with special reference to the tribe Paullinieae in an attempt to improve the understanding of the evolution of the family. The aspects treated are the basic chromosome numbers, the polyploidy and the karyotypes in relation to the systematic in Paullinieae.